A Modified Reactive Powder Concrete Made with Fly Ash and River Sand: An Assessment on Engineering Properties and Microstructure - Huynh, Trong-Phuoc; Ngo, Si-Huy; Nguyen, Van-Dung (Periodica Polytechnica Civil Engineering, 2024)
Containing a high quantity of both fine powders and steel fiber makes reactive powder concrete (RPC) a unique kind of ultra-high strength concrete. However, the cost of manufacture, shrinkage, and hydration heat are increased when silica fume and cement are used in significant amounts. To mitigate these negative consequences and the environmental impact, this study assessed the use of fly ash (FA) with high volume combined with natural-fine river sand (NFRS) in the manufacturing of RPC. FA was utilized to partially substitute cement at 0, 20, 40, and 60 wt% in RPC mixtures that had a set water/binder ratio of 0.2. Thermal conductivity, porosity, water absorption, and compressive strength tests were performed. Furthermore, RPC’s microstructure was examined using a scanning electron microscope (SEM). This study also included a cost and global warming potential analysis of RPC production. Test results indicated that a modified RPC with a 60 MPa compressive strength value could be created by using NFRS and a large amount of FA. In comparison to the reference mixture, a higher compressive strength, reduced water absorption, and lesser porosity were observed in RPC when the FA replacement amount was less than 40%. Many FA particles did not engage in the hydration reaction when the FA replacement level was more than 40%, which had a detrimental impact on the RPC’s characteristics. In general, using FA to produce RPC has certain benefits for the economy and the environment. It is recommended that 40% of FA be used in actual practice.